Results of laparoscopic choledocholithoextraction and choledochoscopy for difficult choledocholithiasis: a single centre experience - Susak, Y. M.; Maksimenko, M. V.; Markulan, L. Y.; Honza, R. V.; Tiuliukin, I. I.; Volkovetskii, V. V. (General Surgery, 2023)
The management of difficult choledocholithiasis, which accounts for 10—15% of all cases of bile duct stones, has not yet been definitively defined. One of the treatment options for difficult choledocholithiasis is laparoscopic choledocholithoextraction combined with choledochoscopy. Objective — to evaluate the experience of a single centre in the treatment of difficult choledocholithiasis using laparoscopic choledocholithoextraction and choledochoscopy. Materials and methods. A total of 47 patients, including 16 (34%) men and 31 (66%) women with difficult choledocholithiasis, were enrolled in the study and received treatment at our centre. All patients were operated on using laparoscopic choledocholithoextraction combined with choledochoscopy. Thereafter, the results of treatment were analysed for the cohort of patients. In the study, we identified the causes of difficult choledocholithiasis and evaluated the achievement of complete bile duct clearance, the surgery duration, total and postoperative bed days, complications, and mortality. Results. All patients underwent laparoscopic choledocholithoextraction combined with choledochoscopy. The causes of difficult choledocholithiasis were as follows: characteristics of bile duct stones — 27 (57.4%), altered anatomy of the organs of the hepatopancreatobiliary zone — 11 (23.6%), specific location of bile duct stones — 9 (19.1%). After laparoscopic choledocholitoextraction combined with choledochoscopy, complete bile duct clearance was achieved in 95.7% of cases. The average duration of the operation was 130.0±14.7 min. The length of hospital stay after surgery was, on average, 14.3±1.7 days. 4 (8.5%) patients had complications corresponding to classes II (2 (4.2%)) and III (2 (4.2%)) according to the standardized Clavien‑Dindo classification (2009). Conclusions. Laparoscopic choledocholithoextraction combined with choledochoscopy can be used as one of the technologies for the treatment of difficult choledocholithiasis.